Carboxymethyl cellulose–alginate interpenetrating hydroxy ethyl methacrylate crosslinked polyvinyl alcohol reinforced hybrid hydrogel templates with improved biological performance for cardiac tissue engineering. Issue 3 (26th November 2022) - Sedighim, Sharona; Chen, Yiqing; Xu, Changlu; Mohindra, Rohit; Liu, Huinan; Agrawal, Devendra K.; Thankam, Finosh G.
Abstract: Cardiac tissue engineering is an emerging approach for cardiac regeneration utilizing the inherent healing responses elicited by the surviving heart using biomaterial templates. In this study, we aimed to develop hydrogel scaffolds for cardiac tissue regeneration following myocardial infarction (MI). Two superabsorbent hydrogels, CAHA2A and CAHA2AP, were developed employing interpenetration chemistry. CAHA2A was constituted with alginate, carboxymethyl cellulose, (hydroxyethyl) methacrylate, and acrylic acid, where CAHA2AP was prepared by interpenetrated CAHA2A with polyvinyl alcohol. Both hydrogels displayed superior physiochemical characteristics, as determined by attenuated total reflection infrared spectroscopy spectral analysis, differential scanning calorimetry measurements, tensile testing, contact angle, water profiling, dye release, and conductivity. In vitro degradation of the hydrogels displayed acceptable weight composure and pH changes. Both hydrogels were hemocompatible, and biocompatible as evidenced by direct contact and MTT assays. The hydrogels promoted anterograde and retrograde migration as determined by the z‐stack analysis using H9c2 cells grown with both gels. Additionally, the coculture of the hydrogels with swine epicardial adipose tissue cells and cardiac fibroblasts resulted in synchronous growth without any toxicity. Also, both hydrogels facilitated the production of extracellular matrix by the H9c2 cells. Overall, the findings support an appreciable in vitro performance of both hydrogels for cardiac tissue engineering applications. Abstract : In vitro performance of CAHA2A and CAHA2AP hydrogels for cardiac tissue engineering applications.